Sustainable Architecture and Construction in Latin America - Flores, Percy (Universidad de Lima. Carrera de Arquitectura, 2021)
DOI: https://doi.org/10.26439/limaq2021.n007.5183 This article explains the current state and advances of sustainable construction in Latin America. In addition, it shows different ways to contribute to sustainability from an architectural perspective: from design criteria to research providing input to such topic. The objective of this research is to promote the importance of sustainable, dignified and efficient buildings for a society facing the challenges of climate change.